Fraud Prevention In Village Financial Management (Literature Review) - Fauziah, Nur Israq; Widyaningsih, Aristanti; Arief, Meta (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2025)
This study aims to identify and synthesize the key factors that influence fraud prevention in village financial management through a systematic literature review. A total of 25 peer-reviewed articles published between 2015 and 2024 were selected using predefined inclusion criteria from reputable databases such as Scopus, Web of Science, and Google Scholar. The findings reveal three major categories of influencing factors: (1) individual and psychological elements, including attitudes, self-awareness, and personal morality; (2) organizational mechanisms, such as internal control systems, ethical organizational culture, human resource competence, whistleblowing systems, accountability, and compensation structures; and (3) external pressures, including coercive, mimetic, and normative pressures. Among these, individual morality and human resource competence emerge as the most critical components for minimizing fraudulent practices. Self-awareness among village officials also plays a vital role in encouraging ethical behavior. The study contributes to the literature by presenting an integrative conceptual framework that links psychological, organizational, and environmental factors affecting fraud prevention in decentralized financial governance. It highlights the importance of fostering ethical cultures and strengthening institutional controls at the village level. Future research should empirically validate the proposed framework and explore regional variations to develop more targeted strategies and policy recommendations for improving transparency and financial accountability in village governance.